Item non-response and imputation of annual labor income in panel surveys from a cross-national perspective - Joachim R. Frick; Markus M. Grabka (Institute for the Study of Labor (IZA), 2007)
Using data on annual individual labor income from three representative panel datasets (German SOEP, British BHPS, Australian HILDA) we investigate a) the selectivity of item non-response (INR) and b) the impact of imputation as a prominent post-survey means to cope with this type of measurement error on prototypical analyses (earnings inequality, mobility and wage regressions) in a cross-national setting. Given the considerable variation of INR across surveys as well as the varying degree of selectivity build into the missing process, there is substantive and methodological interest in an improved harmonization of (income) data production as well as of imputation strategies across surveys. All three panels make use of longitudinal information in their respective imputation procedures, however, there are marked differences in the implementation ...
Keywords: 330; Item non-response; imputation; income inequality; income mobility; panel data; SOEP; BHPS; HILDA; Lohn; Haushaltseinkommen; Statistische Erhebung; Panel; Befragung; Statistischer Fehler; Einkommensverteilung; Soziale Mobilität; Deutschland; Großbritannien; Australien